QT wave dispersion in patients with panic disorder - Atmaca, Murad; Yavuzkir, Mustafa; Izci, Filiz; Gurok, M. Gurkan; Adiyaman, Sahin (Springer, 2012)
QT dispersion (QTd), defined as the maximal inter-lead difference in QT intervals on 12 leads of the surface electrocardiogram (ECG), reflects the regional heterogeneity of ventricular repolarization and has been suggested as an important marker for risk of arrhythmia in addition to the QT interval. Some investigators proposed that it might be a predisposing factor for arrhythmic events and sudden death. Thus, we aimed to investigate whether QTd differs in patients with panic disorder from that in healthy controls. In 40 panic disorder patients and 40 healthy controls, Q(max), Q(min), and QTd values were measured. In addition, the Hamilton depression rating scale and the panic agoraphobia scale were scored for both patients and healthy volunteers. Q(max) and Q(min) values in the panic disorder patients were significantly higher than those in healthy controls. The mean corrected QTd was significantly greater in the patients than in the controls. One-way analysis of covariance (ANCOVA; using left atrial size, age and heart rate as covariates) also corrected the significant difference. In addition, ANCOVA revealed a significant main effect for the diagnosis, indicating a significantly higher QTd for patients compared with controls. QTd might be associated with panic disorder. Future studies in larger samples evaluating the effects of treatment are required.
Keywords: QT dispersion; panic disorder